Analisis Perbedaan Kepuasan Pembaca Tabloid Gratis Surabaya Shopping Media dan Iklan Pos di Surabaya - Marta, Rustono Farady (Institute of Research and Community Outreach - Petra Christian University, 2013)
The underlying motive for someone to read is an attempt to obtain gratification through the media. According to Denis McQuail, there are four typology motives that are used, namely: motive of information (surveillance), motive of personal identity, patterns of integration and social interaction (personal relationship), and entertainment motive (diversion). This study is based on the uses and gratifications theory by analyzing the motives through pre-test questionnaire as an instrument of gratification sought, then post-test questionnaire to determine the real satisfaction (gratification obtained) towards 100 respondents who are included. Quantitative method is used to prove the hypothesis of the study, in which the McNemar test on nominal data for the same population assesses two different objects show the existence of the gap (discrepancy) between the motives with the satisfaction of the reader. This research does not stop until the analysis of the gap between motives and reader satisfaction, but further study to see comparative advertising in the free tabloids